Impact of HLA‐Mismatch in Unrelated Donor Hematopoietic Stem Cell Transplantation: A Meta‐Analysis - Kekre, Natasha; Mak, Kimberley S.; Stopsack, Konrad H.; Binder, Moritz; Ishii, Kazusa; Brånvall, Elsa; Cutler, Corey S. (American journal of hematology, 2016)
The magnitude of risk associated with 9/10 mismatched unrelated donor (MMURD) hematopoietic stem cell transplantation and that of mismatches at the individual HLA loci remain unclear. We performed a meta‐analysis to assess the difference in clinical outcomes between matched unrelated donor (MUD) and MMURD transplantation. A comprehensive search of Medline and Embase for manuscripts regarding transplantation outcomes in primarily adult patients with hematologic malignancies was performed. The pooled effect estimates were calculated using DerSimonian‐Laird random effects models. A total of 13 studies were included, reporting on 13,446 transplants. 9/10 MMURD transplantation was associated with worse overall survival compared to 10/10 MUD transplantation (pooled HR: 1.27, 95% CI: 1.12–1.45; n = 7 studies). Mismatch at HLA‐A, ‐B, or ‐C was associated with significantly worse overall survival compared to MUD transplantation, while there was no significant difference associated with ‐DQ or ‐DPB1 mismatch. Inferior survival associated with HLA‐DRB1 mismatch could not be ruled out. Data on acute and chronic graft‐versus‐host disease were scarce but favored MUD transplantation. In summary, this meta‐analysis of the available literature favored MUD over MMURD transplantation in hematologic malignancies and further quantifies the risks associated with specific HLA‐allele mismatches. Am. J. Hematol. 91:551–555, 2016. © 2016 Wiley Periodicals, Inc.